(untitled) (Indian Journal Of Clinical Practice, 2023)
The glucagon-like peptide-1 receptor agonists (GLP-1RAs) have important beneficial effects on glycemic control and body weight along with their pleiotropic effects on various systems of the body. However, until now these agents were administered via an injection posing a challenge to patient convenience. Oral semaglutide is a first in class oral GLP-1RA co-formulated with an absorption enhancer for the treatment of type 2 diabetes mellitus (T2DM). The clinical efficacy and safety of oral semaglutide has been extensively evaluated in the Peptide InnOvatioN for Early diabEtes tReatment (PIONEER) program of clinical trials. This review shall elaborate on the unique diabetes situation in India and why the oral GLP-1RA (semaglutide) will be a game-changer in the Indian setting.